(untitled) (Journal of the College of Basic Education, 2023)
A number of historical studies dealt with important aspects of the history of the Ottoman Empire during the last half century of its life, which was full of important pivotal changes at the Ottoman and international levels. The rule of Sultan Abdul Hamid II, which began in the early years of that era and lasted thirty-three years, witnessed radical transformations. In the structure of the Ottoman Empire and its internal and external policies. And the rule of the Unionists, which followed it, knew such transformations, the most prominent of which was the policies of democratic transformation of the state and the system of government that prevailed in it, and the alliance with Germany, the emerging global power at the level of the Ottoman foreign policy.